Separating interfering cells from samples using different paramagnetic bead surface compositions for GenomEra® MRSA/SA Multi Swab assay - Wallenius, Maria (My University, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) is a bacterium that is resistant to several antibiotics. MRSA causes a wide range of infections, and because of its resistance to several antibiotics, the infections MRSA cause can be life-threatening, and can lead to epidemics. Carriers of MRSA are usually isolated from other patients in hospitals. Fast and correct diagnosis of MRSA is important to control the spread of MRSA and to avoid the treatment of MRSA with antibiotics that are not effective. Abacus Diagnostica has developed an MRSA/SA Multi Swab assay that detects MRSA and is based on polymerase chain reaction (PCR). It detects both a sequence specific for S. aureus and for antibiotic resistance causing gene mecA. Negative results are reliable, but positive results need to be confirmed, because false positive results arise in a situation where in the sample there are both S. aureus and methicillin-resistant coagulase-negative staphylococci (MRCoNS). MRCoNS bacteria also harbor the antibiotic resistance gene mecA, so the assay detects both target amplicons, and the result is false positive. The aim of the study was to improve the specificity of the assay by separating the interfering cells from the samples using different paramagnetic beads coated with different binders specific for S. aureus cells. Beads tested were carboxyl, epoxy, and tosyl-activated beads. The beads were coated with IgG, anti-protein A antibody and capture probes. All beads tested reduced the sensitivity of the assay, and there was considerable variation in the results. The best worked epoxy beads coated with anti-protein A antibody, whereas carboxyl beads did not function at all, because there was significantly nonspecific binding on the beads. Tosyl-activated beads were non-sensitive. The separation technique using epoxy beads could be improved by adding more different binders on the beads. All in all, more testing would be needed to draw any definite conclusions of this technique.
Keywords: Staphylococcus aureus, MRSA, PCR, paramagnetic beads